13‐4: Passively Addressed Helix‐Free Ferroelectric Liquid Crystal for Fast Response Bi‐Stable Display. Issue 1 (29th May 2019) - Sun, Zhibo; Srivastava, Abhishek; Cheung, Alex; Vashchenko, Valerii; Kwok, Hoi-Sing
Abstract : A helix free ferroelectric liquid crystal (FLC) panel using the passively addressed driving scheme has been realized. The FLC layer thickness is 4um. Asymmetric boundary conditions have been used for providing high contrast and steady multiplex operation. The electro‐optical performance of the panel shows fast switching time around 87us and good bi‐stability in the meantime. A 4um 64*64 passively addressed FLC display prototype has been achieved and successfully multiplexed.